Love of Money, Idealisme pada Persepsi Etis Mahasiswa Akuntansi dengan Kecerdasan Inteletual sebagai Variabel Moderasi - Rinaldi, Muhammad Bagas; Dewi, Luh Gede Krisna (E-Jurnal Akuntansi; Vol 33 No 9 (2023), 2023)
This research aims to examine the influence of love of money and idealism on accounting students' ethical perceptions with intellectual intelligence as a moderating variable. Testing was carried out on accounting students from the Accounting Study Program, Faculty of Economics and Business, Udayana University class of 2017. The sample was selected using the purposive sampling method. The minimum number of samples was determined using the Slovin formula, which resulted in a sample size of 109 individuals. The data collection method in this research used a questionnaire method, and the data was analyzed using multiple linear regression models and moderated regression analysis (MRA). The results of the analysis show that there is no significant relationship between love of money and accounting students' ethical perceptions. However, idealism has a positive influence on accounting students' ethical perceptions. Intellectual intelligence does not moderate the relationship between love of money and idealism in accounting students' ethical perceptions.Kata Kunci: love of money , idealisme, kecerdasan intelektual, persepsi etis. Keywords: love of money; idealism; intellectual intelligence; ethical perceptions.